Tregs Attenuate Peripheral Oxidative Stress and Acute Phase Proteins in ALS. Issue 2 (7th May 2022) - Beers, David R.; Thonhoff, Jason R.; Faridar, Alireza; Thome, Aaron D.; Zhao, Weihua; Wen, Shixiang; Appel, Stanley H.
Abstract : Oxidative stress (OS) induces inflammation, which in turn exacerbates OS and the expression of acute phase proteins (APPs). Regulatory T lymphocyte (Treg) therapy was assessed for suppression of OS and APP responses in longitudinal serum samples from subjects with amyotrophic lateral sclerosis (ALS) enrolled in a phase I clinical trial. The first round of Treg therapy suppressed levels of oxidized low‐density lipoprotein (ox‐LDL). During a 6‐month washout period, ox‐LDL levels increased. A second round of therapy again suppressed ox‐LDL levels and then rose following the cessation of treatment. Serum levels of APPs, soluble CD14, lipopolysaccharide binding protein, and C‐reactive protein, were stabilized during Treg administrations, but rose during the washout period and again after therapy was discontinued. Treg therapy potentially suppresses peripheral OS and the accompanying circulating pro‐inflammatory induced APPs, both of which may serve as peripheral candidates for monitoring efficacies of immunomodulating therapies. ANN NEUROL 2022;92:195–200